Canine Distemper Virus in Autochtonous and Imported Dogs, Southern Italy (2014–2021) - Flora Alfano; Gianvito Lanave; Maria Gabriella Lucibelli; Gianluca Miletti; Nicola D’Alessio; Amalia Gallo; Clementina Auriemma; Maria Grazia Amoroso; Maria Stella Lucente; Esterina De Carlo; Vito Martella; Nicola Decaro; et al. (Animals, 2022)
This study aims to investigate the presence of canine distemper virus (CDV) infection in 949 autochthonous or illegally imported dogs from Southern Italy, over a period of eight years (2014–2021). CDV RNA was detected in 6.8% (65/949) of the animals tested, with no detection of CDV in dogs sampled in 2020–2021. The frequency of CDV detection was higher in imported dogs (19/103, 18.3%) with respect to stray (27/365, 7.4%) and household dogs (19/481, 3.9%). On sequence and phylogenetic analyses of selected strains, the analyzed viruses belonged to the Arctic clade, which has already been reported in Italy and in Europe. The results of our study may suggest a reduction of CDV circulation in Southern Italy, while at the same time highlighting the need for strict controls on dog importation, in order to prevent the introduction of viruses from endemic countries.